2005
DOI: 10.1093/jn/135.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Gene Expression Profiles Are Altered by Genistein Supplementation in Mice with Diet-Induced Obesity

Abstract: We reported previously that genistein enhances the expression of genes involved in fatty acid catabolism through activation of peroxisome proliferator-activated receptor (PPAR) alpha in HepG2 cells, suggesting that genistein holds great promise for therapeutic applications to lipid abnormalities such as obesity and hyperlipidemia in humans. In this study, we examined the changes in hepatic transcriptional profiles using cDNA microarrays in mice with high-fat diet (HFD)-induced obesity supplemented with geniste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
67
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 42 publications
14
67
0
Order By: Relevance
“…In general, microarray data published so far supports existing hypotheses on the mechanisms of action of genistein, both beneficial for human health (i.e. reduction of cancer risk, amelioration of postmenopausal syndrome and decrease of bone resorption in postmenopausal women, lipid metabolism, cardiovascular homeostasis) (Kim et al, 2005;Lee et al, 2007;Pie et al, 2006;Rice et al, 2007) and unfavorable (as estrogen-dependent cancer cell proliferation and adverse effects on the reproductive organs or involution of thymus and auto-immune disorders) (Lee et al, 2007;Naciff et al, 2002;Selvaraj et al, 2005). Those homeostasis-maintaining or homeostasis-affecting effects are often observed at low concentrations of genistein, essentially not exceeding 5 M.…”
Section: Signalling Pathways Influenced By Genistein In Microarrays Psupporting
confidence: 70%
See 3 more Smart Citations
“…In general, microarray data published so far supports existing hypotheses on the mechanisms of action of genistein, both beneficial for human health (i.e. reduction of cancer risk, amelioration of postmenopausal syndrome and decrease of bone resorption in postmenopausal women, lipid metabolism, cardiovascular homeostasis) (Kim et al, 2005;Lee et al, 2007;Pie et al, 2006;Rice et al, 2007) and unfavorable (as estrogen-dependent cancer cell proliferation and adverse effects on the reproductive organs or involution of thymus and auto-immune disorders) (Lee et al, 2007;Naciff et al, 2002;Selvaraj et al, 2005). Those homeostasis-maintaining or homeostasis-affecting effects are often observed at low concentrations of genistein, essentially not exceeding 5 M.…”
Section: Signalling Pathways Influenced By Genistein In Microarrays Psupporting
confidence: 70%
“…7OH group of genistein forms hydrogen bonds with the glutamate in helix 3, the arginine in helix 5, and a water molecule; 4'OH group forms hydrogen bond with H398. Adapted and reprinted by permission from American Association for Cancer Research, Suetsugi et al 2003, Molecular Cancer Research Vol.1, No.13, 981-991. Other members of nuclear receptor family activated by genistein are peroxisome proliferatorsactivated receptor  (PPAR) (Dang et al, 2003) and PPAR (Kim et al, 2004;Kim et al, 2005). The main role of PPAR is to control the genes involved in adipocyte differentiation and lipid storage.…”
Section: Binding Of Genistein To Different Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Besides these results, our hepatic transcript profiles showed that daidzein supplementation reduced hepatic lipid levels through the activation of ACAS and ACAD, which are involved in fatty acid b-oxidation, [42][43][44][45][46][47] and this activation was due to the upregulation of PPARa, their upstream gene. 48 Daidzein supplementation also functions as hepatic antisteatotic materials by the regulation of adipocyte metabolism. Recently, adiponectin has been shown to exert protective effects against NAFLD in obese ob/ob mice, 49 hepatic injury or fibrogenesis in mice to whom lipopolysaccharide or CCl 4 were administered.…”
Section: Discussionmentioning
confidence: 99%